Adolescent health survey Terengganu 1999 - Nordiyanah H.,; Khatijah A.R.,; M. Kamil H.M. ,; Aris. K.,; Mohammad J., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2001)
The objective is to determine the prevalence of risk behaviour among 15-year-old adolescents and to identify related protective or risk factors. It was a cross sectional study involving 758 adolescents at the age of 15 years old, 384 males and 374 females in the District Kuala Terengganu and Besut. Pre-prepared self-administered questionnaire was used to determine measures chosen. The results indicated that about 12.8% (10.9% males, 1.9% females) adolescents were ever smoked, 2.0% (1.7% males, 0.3% females) ever involved in sexual activities and 37.3% (20.1% males and 17.3% females) ever involved in physical fight. Feel connected to parents and had dinner everyday with family were protective against every health risk behaviour for both sexes except for sexuality among girls. Felt satisfied with day-today life, rarely felt boredom or depressed and never had a feeling to run away from home reduced likelihood of adolescent engaging in sexual activity and physical fight.Practice good behaviour with parents and siblings at home was protective for both sexes. Conversely, ever missed class or schools (p<0.001) were factors against risk behaviour for both gender. Presence of family members smoking was associated with smoking for girls (p<0.05) and boys (p<0.05). Parents who did not give attention to whom their children’s companion were associated with smoking (p<0.05) sexual debut (p<0.05) in boys and physical fight for both gender, p < 0.05 and p<0.01 for boys and girls respectively. In conclusion family, individual and peer characteristics are associated with both protective and risk factors; religiousity is protective while negative peer influence was risk factor for adolescents. The findings of the study will enable programme planner to plan for intervention activities in order to enhance protective factors and to minimize risk factors in the three domains.